Experiences of Young and Middle-Aged Stroke Patients with Hemiplegia Who Actively Participate in Rehabilitation Exercises and Their Perceptions of Well-Being: A Descriptive Qualitative Study - Si Y; Huang X; Zhao S; Ou Z; Pi M; Du J (Risk Management and Healthcare Policy)
Yumeng Si,1,2 Xingxian Huang,2 Shiting Zhao,2 Ziyang Ou,2 Min Pi,2,* Jing Du2,* 1Anhui University of Chinese Medicine, Hefei, 230012, People’s Republic of China; 2Shenzhen Traditional Chinese Medicine Hospital, Shenzhen, 518033, People’s Republic of China*These authors contributed equally to this workCorrespondence: Jing Du, Email 57396171@qq.com Min Pi, Email pppimin@qq.comBackground: Young and middle-aged stroke patients who suffer from neurological deficits brought on by hemiplegia experience significant physical and psychological effects.This study was designed to explore the experience of these patients during active participation in rehabilitation exercises and their perception of well-being. The purpose was to inform the clinical development of individualized rehabilitation programs.Methods: Purposive sampling was employed to conduct semi-structured, in-depth interviews with 16 young and middle-aged stroke hemiplegic patients (18– 59 years old) using a descriptive qualitative research approach. Thematic analysis was used for data analysis.Results: Five core themes were identified: (1) motivation for the rehabilitation movement, (2) the importance of the rehabilitation environment, (3) challenges for the rehabilitation movement, (4) psychological dynamics and growth in rehabilitation, and (5) rehabilitants’ unique perception of well-being. In addition, it is important to note that, the well-being of the majority of the young and middle-aged stroke patients with hemiplegia in this study remained substantially reduced after the disease despite the fact that they were actively engaged in rehabilitation exercises.Conclusion: Young and middle-aged stroke patients with hemiplegia who actively participate in rehabilitation have a variety of needs and experiences. Their rehabilitation process includes not only the restoration of physical function but also the reconstruction of psychological adaptability and the dynamic transformation of well-being. Nonetheless, the current rehabilitation system has glaring flaws when it comes to considering the combined benefits of psychological and physical therapies. In order to remedy the situation, it is advised that well-being be included in stroke rehabilitation, that commonly used rehabilitation and psychological intervention programs be covered by health insurance, as well as reimbursement rates be raised. In this way, a system of health care coverage and support for patients’ complete recovery will eventually be built.Keywords: stroke, hemiplegia, rehabilitative, well-being, qualitative study